2013
DOI: 10.1002/oby.20308
|View full text |Cite
|
Sign up to set email alerts
|

Associations between accelerometer-derived physical activity and regional adiposity in young men and women

Abstract: Objective Empirical evidence supports an inverse relationship between physical activity (PA) and adiposity, but studies using detailed measures of both are scarce. We described the relationship between regional adiposity and accelerometer-derived PA in men and women. Design and Methods Cross-sectional analysis included 253 participants from a weight loss study limited to ages 20–45 years and BMI 25–39.9 kg/m2. PA data were collected with accelerometers and expressed as total accelerometer counts and average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 31 publications
3
14
1
Order By: Relevance
“…Our findings are consistent with other, smaller studies that have also reported sex differences when examining the association between sedentary behaviors and abdominal fat deposition (13, 26, 31). For example, Henson and colleagues reported positive associations between accelerometer measured sedentary time and magnetic resonance imaging measured VAT and liver fat in a sample of 66 White men and women at risk for type 2 diabetes (13).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are consistent with other, smaller studies that have also reported sex differences when examining the association between sedentary behaviors and abdominal fat deposition (13, 26, 31). For example, Henson and colleagues reported positive associations between accelerometer measured sedentary time and magnetic resonance imaging measured VAT and liver fat in a sample of 66 White men and women at risk for type 2 diabetes (13).…”
Section: Discussionsupporting
confidence: 92%
“…A study by Yim and colleagues found stronger associations between IMAT and glucose, protein bound glucose, and total cholesterol than observed for VAT (33). Adverse associations have also been reported between liver fat and fasting glucose and triglycerides, independent of other fat depots (31). In our study, we found that among White men, total sedentary time and television viewing were adversely associated with IMAT and liver attenuation, while the opposite associations were observed for physical activity and these fat depots in the entire cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is also in agreement with previous evi dence that SED is positively associated with waist circum ference independent of MVPA (10). A further study of 2056 European healthy middle-age adults found a positive as sociation between SED measured using accelerometry and anthropometric measures including waist circumference (32), and Smith et al (22) found a significant positive as sociation between SED and VAT in women. Other studies did not find such associations, but these are characterized by smaller study samples and/or self-reported PA assess ment (15,20).…”
Section: Discussionsupporting
confidence: 90%
“…In a cross-sectional analysis of 253 young adults, Smith et al (22) found that PA volume assessed as total accelerometer counts was not associated with VAT measured with computed tomography. They also did not find a significant association between MVPA and VAT in an analysis where all intensity categories are in cluded in the same model, that is, an analysis similar to ours.…”
Section: Discussionmentioning
confidence: 99%